RATIO LEGIS OF INTERFAITH INHERITANCE REFORMULATION FROM THE PERSPECTIVE OF FIQH MINORITY: A STUDY OF THE THOUGHTS OF YUSUF AL-QARDHAWI AND TAHA JABIR AL-ALWANI - As-Suvi, Ahmad Qiram; Zuhriah, Erfaniah (Jurnal Pembaharuan Hukum, 2023)
This article aims to delve deeply into the ratio legis of reformulating the legal status of interfaith inheritance from the perspective of fiqh minority, as articulated by the thoughts of Yusuf al-Qardhawi and Taha Jabir al-Alwani. The research method employed in this article is a library research approach, utilizing comparison and content analysis to identify similarities, differences, and potential points of convergence in their thinking. The research findings indicate that the legal status of interfaith inheritance, according to the fiqh minority of Qardhawi and Alwani, must be redefined from the classical textual fiqh formulations to a contextual division of interfaith inheritance. The growing Muslim population in various non-Muslim countries necessitates the urgent reformulation of interfaith inheritance distribution to fill the normative vacuum within minority Muslim communities. The ratio legis of reformulating the legal status of interfaith inheritance according to Qardhawi and Alwani is based on considerations of maslahat (public interest) and the values of Maqashid al-Shariah, which serve as guiding principles for redefining the contextual legal status of interfaith inheritance. Failure to understand Islam solely through a textual lens and an inability to address the issues faced by minority Muslims in non-Muslim countries could relegate Islamic law to a relic of civilization.